2020
DOI: 10.1016/j.envpol.2020.115024
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts the subsurface transport of atrazine and estrone originating from agricultural production activities

Abstract: Climate change will impact soil properties such as soil moisture, organic carbon and temperature and changes in these properties will influence the sorption, biodegradation and leaching of trace organic contaminants to groundwater. In this study, we conducted a modeling case study to evaluate atrazine and estrone transport in the subsurface under current and future climate conditions at a field site in central Nebraska. According to the modeling results, in the future, enhanced evapotranspiration and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In general, when the degradation rate is higher, climate variability has minimal impacts on the atrazine mass accumulation. Under a drier condition, reduced biodegradation of atrazine in the water phase is reported 34 and may exacerbate atrazine accumulation. Further studies on factors changing the atrazine degradation rate are suggested.…”
Section: Coeffects Of Transport Parameter and Climatementioning
confidence: 99%
“…In general, when the degradation rate is higher, climate variability has minimal impacts on the atrazine mass accumulation. Under a drier condition, reduced biodegradation of atrazine in the water phase is reported 34 and may exacerbate atrazine accumulation. Further studies on factors changing the atrazine degradation rate are suggested.…”
Section: Coeffects Of Transport Parameter and Climatementioning
confidence: 99%
“…However, this herbicide has harmful effects on sensitive crops such as wheat, soybean, and rice [4]. Atrazine is easily retained in the soil and readily leaches into the deeper soil with rain due to its long half-life and low soil Diversity 2021, 13, 259 2 of 17 absorption rate [5][6][7]. Jablonowski et al (2009) reported that atrazine and its degradation products were still detected in soils 22 years after its application [8].…”
Section: Introductionmentioning
confidence: 99%